Thyroid storm following anterior cervical spine surgery for Koch's spine - Huzurbazar, Sanjiv (Medknow Publications & Media Pvt Ltd, 2014)
The primary objective was to report this rare case and discuss the probable mechanism of thyroid storm following anterior cervical spine surgery for Kochs cervical spine.